A Nationwide Population-Based Cohort Study of Migraine and Organic-Psychogenic Erectile Dysfunction. Issue 10 (March 2016) - Wu, Szu-Hsien; Chuang, Eric; Chuang, Tien-Yow; Lin, Cheng-Li; Lin, Ming-Chia; Yen, Der-Jen; Kao, Chia-Hung
Abstract : Abstract: As chronic illnesses and chronic pain are related to erectile dysfunction (ED), migraine as a prevalent chronic disorder affecting lots of people all over the world may negatively affect quality of life as well as sexual function. However, a large-scale population-based study of erectile dysfunction and other different comorbidities in patients with migraine is quite limited. This cohort longitudinal study aimed to estimate the association between migraine and ED using a nationwide population-based database in Taiwan. The data used for this cohort study were retrieved from the Longitudinal Health Insurance Database 2000 in Taiwan. We identified 5015 patients with migraine and frequency matched 20, 060 controls without migraine from 2000 to 2011. The occurrence of ED was followed up until the end of 2011. We used Cox proportional hazard regression models to analyze the risks of ED. The overall incidence of ED was 1.78-fold greater in the migraine cohort than in the comparison cohort (23.3 vs 10.5 per 10, 000 person-years; 95% confidence interval [CI] = 1.31–2.41). Furthermore, patients with migraine were 1.75-fold more likely to develop organic ED (95% CI = 1.27–2.41) than were the comparison cohort. The migraine patients with anxiety had a 3.6-fold higher HR of having been diagnosed with ED than the comparison cohort without anxiety (95% CI, 2.10–6.18). The results support that patients with migraine have a higher incidence of being diagnosed with ED, particularly in the patient with the comorbidity of anxiety.